HUBUNGAN BAURAN PEMASARAN DENGAN KEPUTUSAN PEMBELIAN DI HOTEL ROCKY PLAZA PADANG - Suryani, Triana; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research aims to determine the relationship between the marketing mix with purchasing decisions in Rocky Plaza Hotel Padang. Type of this research is correlational. The population in this research are all peoples who are and have been and use the facilities at Rocky Plaza Hotel Padang, amounting to 6583 people. The sampling technique in this research is incidental sampling by 99 guests. The data collection techniques with indirect communication by distributing a questionnaire using Likert scale and have been tested for validity and reliability. The results of this research showed that there is a positive relationship (strong) and significant correlation between the marketing mix with purchasing decisions which are judged by a guest at Rocky Plaza Hotel Padang with r scale 0.819 are at r table> 0,75- 0,99 and at the level of 0.000 Sig. This means that the better the marketing mix implemented, the better the purchasing decisions in Rocky Plaza Hotel Padang, vice versa.